The Effect of Artificial Intelligence on Student Confidence in Online Adult Learning: A Meta-Analysis and Systematic Review - English, Vincent (International Journal of Educational Studies, 2025)
The integration of Artificial Intelligence (AI) into online education is rapidly transforming learning environments, particularly for adult learners. While AI promises personalized and efficient educational experiences, its impact on crucial affective domains, such as student confidence and self-efficacy, remains underexplored. Confidence is a critical determinant of persistence, engagement, and success in adult learning. This meta-analysis and systematic review synthesizes current empirical evidence to evaluate the effect of AI-powered tools and platforms on student confidence in online adult learning contexts. A systematic search of major academic databases was conducted to identify peer-reviewed studies published between 2019 and 2025 that investigated AI interventions in online adult education and measured outcomes related to student confidence or self-efficacy. Following PRISMA guidelines, we screened and selected studies for inclusion. We performed a quantitative synthesis of reported effect sizes and a qualitative thematic analysis to identify the mechanisms through which AI influences learner confidence. Our analysis of the included studies reveals a predominantly positive and significant effect of AI on student confidence. A quantitative synthesis of studies providing effect sizes revealed a large, positive impact (mean Cohen's d = 1.24). The thematic analysis identified four key mechanisms: (1) Enhanced scaffolding and personalized support, where AI provides immediate, non-judgmental feedback that builds mastery; (2) Fostering autonomy and self-directed learning, empowering learners to take control of their educational journey; (3) The double-edged sword of dependence, where over-reliance on AI can potentially undermine intrinsic confidence; and (4) The amplification of human connection, where AI tools, when used effectively, free up instructor time for more meaningful, confidence-building interactions. When thoughtfully designed and implemented, AI technologies can be powerful tools for enhancing confidence among online adult learners. The most effective interventions are those that use AI to augment, rather than replace, human instruction, providing personalized support while fostering learner autonomy. These findings provide crucial insights for educators, instructional designers, and policymakers seeking to harness AI to create more supportive and empowering online learning environments for adults.